Investigating Rainfall Patterns in the Hubei Province, China and Northern Italy During the Covid-19 Lockdowns - Sharif, Ridwana Binte; Houser, Paul; Aquila, Valentina; Maggioni, Viviana (Frontiers in Climate, 2022)
In the spring of 2020, many countries enacted strict lockdowns to contain the spread of the 2019 coronavirus disease (COVID-19), resulting in a sharp observed decrease in regional atmospheric pollutant concentrations, such as NOx and aerosols in early 2020. Atmospheric composition can influence cloud properties and might have a significant effect on the initiation of precipitation. This study investigated changes in precipitation patterns during COVID-19 lockdowns and compared them to patterns observed during the previous 19 years (2001 through 2019) across two regions of interest, the Hubei province in China and Northern Italy using a satellite-based precipitation dataset. Results indicated that overall rainfall averages were higher in the spring of 2020 with respect to their corresponding climatological means, with higher standard deviations especially in the more urbanized regions like Wuhan, China and Milan, Italy. Precipitation rates observed during the Spring of 2020 tend to fall outside of the climatological 25th-75th percentile bounds. Similarly, the number of rainy pixels was in several cases in Spring 2020 higher than the climatological 75th percentile and sometimes even higher than the 95th one. These anomalies may be due to natural variations and may not be caused directly by the reduction in atmospheric pollutant concentrations. Nevertheless, our analysis proved that precipitation patterns during the lockdowns were on the extreme tails of the precipitation climatological distributions for both regions of interest. Lastly, decorrelation lags and distances in Northern Italy remained similar to their corresponding climatological values, whereas in the Hubei province some differences were observed, with the Spring 2020 spatial correlation variogram almost overlapping the climatological 5th percentile and with a decorrelation distance shorter than the climatological value.